Bistable Multi‐Layer Triboelectric Nanogenerator for Harvesting Random and Ultra‐Low‐Frequency Vibration Energy with Increased Charge Transfer - Yi Guan; Xin Li; Zehan Wei; Mianxin Xiao; Zhihui Lai; Shuxiang Dong; Daniil Yurchenko; Shitong Fang (Advanced Science)
Abstract Approximately 70% of the Earth’s surface is covered by seawater, making the ocean ideal for harvesting energy. Triboelectric nanogenerators (TENGs), due to their low cost and simple structure, are well‐suited for capturing ocean energy. However, their low charge transfer under weak inputs limits efficiency in harvesting random and ultra‐low‐frequency wave energy. This paper proposes a novel bistable multi‐layer TENG (BM‐TENG) to address this challenge for self‐powered wireless sensing and lighting. Simulations and experiments demonstrate that both in intra‐well and inter‐well motions, the bistable mechanism enhances the dynamic responses and thus the power output by up to 48%. Furthermore, the multi‐layer design within the constrained structure significantly boosts the power density. Experimental results show 730 V peak‐to‐peak open‐circuit voltage and 5 mW maximum power in a three‐layer BM‐TENG under the excitation of 0.6 Hz and 0.18 g. The normalized power density of the proposed device is 54.9 Wm−3·Hz−1, surpassing the state‐of‐the‐art results in literature. The application test shows that BM‐TENG can successfully power 296 LEDs for ocean warning lighting, and power Bluetooth wireless sensors for monitoring marine environmental variables. This work introduces a novel and highly efficient self‐powered sensing technique for advancements in marine Internet of Things (IoT) systems.